Influence of Bacterial Inoculants and Xylanase on Silage Fermentation Characteristics of Wheat Straw and Green Maize Silage - Belim, Saman Y.; Savsani, Harish H.; Chavda, Mitesh R.; Odedra, Mulraj D.; Kansagara, Yash G.; Agravat, Priyam H. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present investigation was conducted with the objective to study various combinations of biological and chemical additives on fermentation characteristics of wheat straw and green maize silage. Different silages were prepared using green maize fodder and wheat straw in the proportion of 10:0 & 7:3 ratio in plastic jar of 3 kg capacity (3 replication in each) by adding common salt @ 0.5%, urea @ 1% and molasses @ 1.5% in each silage with seven different treatments, viz., Control (only green maize), WS (green maize and wheat straw in 7:3 ratio), X (WS added with Xylanase), LP (WS added with  Lactobacillus plantarum), LF (WS added with Lactobacillus fermentum), LPLF (WS added with both bacterial inoculants) and XLPLF (WS added with Xylanase and both bacterial inoculants). Xylanase, L. plantarum and L. fermentum were used @ 1500 IU/g, 1 x 106 cfu/g and 2 x 106 cfu/g, respectively. All silages were evaluated for silage fermentation characteristics after 45 days of ensiling. The results revealed that the pH values of different experimental silages were recorded significantly (p
Keywords: L. fermentum; L. plantarum; Silage; Wheat straw; Xylanase